MALPRACTICE IN PSYCHOLOGICAL SERVICES: A CASE STUDY OF SEXUAL HARASSMENT FROM THE PERPETRATOR'S PERSPECTIVE - Martin, Ricky Alejandro; Matulessy, Andik (UNG, 2024)
Sexual harassment is a despicable act, but sadly, it often happens. Cases of sexual harassment are increasing every year. The purpose of writing this research is to dig deeper into the sexual harassment committed by psychology practitioners. This research is a qualitative research case study. The data from this study were obtained through observation and interviews with both subjects at different times and places. This study involved two psychology practitioners as subjects. The results of the study found three main themes: The intensity of the emergence of sexual harassment more than 10 times a year, and the types of sexual harassment are verbal and physical. The subject's motives in committing sexual harassment were opportunities, a supportive environment, and the satisfaction of personal.